Cost-Effectiveness of an Intensive Upper Limb Rehabilitation Therapy for Children With Unilateral Cerebral Palsy: An Economic Evaluation of a Randomized Controlled Trial - Michael C. David; Hideki Higashi (Journal of Health Economics and Outcomes Research)
**Background:** Unilateral cerebral palsy is a major cause of childhood disability and a substantial economic burden. Intensive group-based therapy, consisting of hybrid constraint-induced movement and bimanual therapies, has been shown to be effective in improving specific quality-of-life domains in children with this disability. Our objective in this study was to assess if this intervention was cost-effective compared with standard care.